Greenland Ice Sheet Rainfall, Heat and Albedo Feedback Impacts From the Mid‐August 2021 Atmospheric River. Issue 11 (2nd June 2022) - Box, Jason E.; Wehrlé, Adrien; van As, Dirk; Fausto, Robert S.; Kjeldsen, Kristian K.; Dachauer, Amrin; Ahlstrøm, Andreas P.; Picard, Ghislain
Abstract: Rainfall at the Greenland ice sheet Summit 14 August 2021, was delivered by an atmospheric river (AR). Extreme surface ablation expanded the all‐Greenland bare ice area to near‐record‐high with snowline climbing up to 788 ± 90 m. Ice sheet wet snow extent reached 46%, a record high for the 15–31 August AMSR data since 2003. Heat‐driven firn deflation averaged 0.14 ± 0.05 m at four accumulation area automatic weather stations (AWSs). Energy budget calculations from AWS data indicate that surface heating from rainfall is much smaller than from either the sensible, latent, net‐longwave or solar energy fluxes. Sensitivity tests show that without the heat‐driven snow‐darkening, melt at 1, 840 m would have totaled 28% less. Similarly, at 1, 270 m elevation, without the bare ice exposure, melting would have been 51% less. Proglacial river discharge was the highest on record since 2006 for late August and confirms the melt‐sustaining effect of the albedo feedback. Plain Language Summary: While rainfall at Summit station atop of the Greenland Ice Sheet in mid‐August 2021 captured global attention, its direct surface thermal effects were weak and unable to explain the major melt and river discharge that occurred during and after the event. Exceptional heating of the ice sheet first occurred due to the heat transfer from condensation and the elevated air temperature during an atmospheric river (AR) episode. Satellite measurements reveal a rapid retreat of the snowline to higher elevations, exposing a large extent of relatively dark bare ice. Where snow remained, darkening due to wet snow metamorphism was responsible for sustained additional solar heating of the upper ice sheet elevations for the following 2 weeks. Observations from automatic weather stations and satellites, and river gauging, reveal that the AR had an immediate and sustained impact. Key Points: A mid‐August 2021 Greenland atmospheric river (AR) produced extreme ice sheet snow cover changes and high proglacial river discharge Surface heating from rainfall is small compared to latent and sensible heating, net longwave radiation or sunlight absorption Melt‐albedo feedback enhanced upper elevations snow melt under clear skies following the heating delivered by the AR